2017
DOI: 10.1016/j.jmii.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor analysis and molecular epidemiology of respiratory adenovirus infections among children in northern Taiwan, 2009–2013

Abstract: HAdV infections circulate all year-round. HAdV B7 is strongly related to severe infections and pneumonia. Underlying neurologic diseases and prematurity are risk factors for severe HAdV infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 22 publications
6
31
1
2
Order By: Relevance
“…Pneumonia was also the most common clinical diagnosis (89%), with half of these patients subsequently developing respiratory failure. A previous study suggested that HAdV-7 is strongly related to severe infections, pneumonia and underlying neurological diseases and is a risk factor for severe HAdV infection [32].…”
Section: Discussionmentioning
confidence: 99%
“…Pneumonia was also the most common clinical diagnosis (89%), with half of these patients subsequently developing respiratory failure. A previous study suggested that HAdV-7 is strongly related to severe infections, pneumonia and underlying neurological diseases and is a risk factor for severe HAdV infection [32].…”
Section: Discussionmentioning
confidence: 99%
“…According to literature, most frequent symptoms associated with severe adenoviral pneumonia are prolonged fever, respiratory compromise with hypoxia and rapid deterioration of clinical condition, requiring intubation and ventilation [20,21]; bilateral interstitial infiltrates are the most common radiological findings [1,4,7]. Lymphopenia, thrombocytopenia and elevated transaminases levels are frequently observed.…”
Section: Discussionmentioning
confidence: 99%
“…Human adenoviruses (HAdVs) are non enveloped, double stranded DNA viruses usually causing acute febrile and self-limiting respiratory infections in children [1,4]. Severe infections are usually observed in neonates [2] and immunocompromised adults, such as HIV-positive individuals or transplanted patients [3,5].…”
Section: Why This Case Is Important?mentioning
confidence: 99%
“…Outbreaks of adenoviral pneumonia have been occasionally reported in young adult women or military personnel [5][6][7][8][9]. Respiratory tract infection is the leading cause of hospitalization of military trainees in the medical field.…”
Section: Introductionmentioning
confidence: 99%